Understanding gift-giving in game live streaming on Douyu: An evaluation of PSR/social presence - Zhang, Wenchi (Frontiers in Psychology, 2022)
In China, live streaming has grown rapidly in recent years, with gift-giving, a unique business model in live streaming, driving the development of many industries. This article explores the association between gift-giving behavior in game live streaming and viewers' live streaming experience. Specifically, this study aims to explore the correlation between Para-social Relationships, Social Presence, and gift-giving in the context of China. Based on the survey and interview of the viewer on Douyu, a Chinese live streaming platform, this study found that there is only a weak to a medium correlation between para-social relationships and viewers’ gift-giving behavior. The correlation between social presence and gift-giving was even weaker. Although the conclusion of this study may be affected by the sample size limitation, it can still provide a reference for the current research on gift-giving on Chinese live streaming platforms.